Screening for Activity Against AMPA Receptors Among Anticonvulsants—Focus on Phenytoin - Dron, M. Y.; Zhigulin, A. S.; Tikhonov, D. B.; Barygin, O. I. (Frontiers in Pharmacology, 2021)
The interest in AMPA receptors as a target for epilepsy treatment increased substantially after approval of perampanel, negative AMPA receptor allosteric antagonist, for the treatment of partial-onset seizures and generalized tonic-clonic seizures. Here we performed a screening for activity against native calcium-permeable AMPA receptors (CP-AMPARs) and calcium-impermeable AMPA receptors (CI-AMPARs) among different anticonvulsants using whole cell patch-clamp method on isolated Wistar rat brain neurons. Lamotrigine, topiramate, levetiracetam, felbamate, carbamazepine, tiagabin, vigabatrin, zonisamide and gabapentin in 100 µM concentration were practically inactive against both major subtypes of AMPARs, while phenytoin reversibly inhibited them with IC50 of 30±4 µM and 250±60 µM for CI-AMPARs and CP-AMPARs respectively. The action of phenytoin on CI-AMPARs was use-dependent and competitive-like. It closely resembled that of pentobarbital, being different from classical competitive inhibitors, negative allosteric inhibitors and CP-AMPARs selective channel blockers. The main target for phenytoin in the brain, which is believed to underlie its anticonvulsant properties, are voltage-gated sodium channels. Here we have shown for the first time that phenytoin inhibits CI-AMPARs with similar potency. Thus AMPAR inhibition by phenytoin may contribute to its anticonvulsant properties, as well as its side effects.